The Effect of Social Support and Self-Efficacy on Interest in Arabic Learning for College Students - Zikri Neni Iska; Kaula Fahmi; Ilham Maulana Amyn; Siti Ummi Masruroh (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This study aims to determine the effect of social support and self-efficacy on interest in learning Arabic in students of the general faculty of UIN Jakarta. This study used quantitative research method, and the population were students of general studies at UIN Jakarta. The samples used in this study were 152 students of the General Study Program of UIN Jakarta. The sampling technique in this study uses a non-probability sampling technique. The measuring tools used in this study are the interpersonal support evaluation list – shortened version, (GSES-12), and Interest in Academic Domain. Test the validity of the measuring instrument used using the (CFA) technique. The results of the hypothesis test show that the value of R Square = 0.50, which means that the proportion of the variance of interest in learning Arabic which is explained by all independent variables is 50.3%, while the other 49.7% is influenced by other variables not examined. Two variables positively and significantly affect interest in learning Arabic, namely tangible support and self-efficacy.